The role of the European Union in the international fight against climate change - Contreras, Delia (Observatorio Medioambiental, 2013)
Although the European Union has been taking effort to assume leadership in the fight against climate change, a number of factors have left exposed defects and weaknesses that minimizing European leadership. In this context, our study aims to evaluate the main parameters on which European Environmental Policy is based to determinate if the organization is legitimized to star in international efforts against global warming.
Keywords: Climate change; global warming; Kyoto Protocol; United Nations Framework Convention on Climate Change; European Union